The Representation of Architectural Space for Caspar David Friedrich: The Case Study of Eldena Abbey - Antonio Esposito (Arts)
The spatiality of Caspar David Friedrich’s paintings has always been a topic of investigation within the field of Romantic art history. This research has been conducted with the objective of gaining insight into the ideas and reasoning of the Greifswald painter. The influence of new insights into Caspar David Friedrich’s spatiality construction has led the scholarship to trigger different ways of interpreting his paintings and artworks. The aim of the proposed study is to analyse the architectural spatiality as defined by Friedrich in his paintings that have Eldena Abbey as their main architectural reference, using a methodology that uses 3D digital modelling as its main tool, in order to understand if the painter used any spatial compositional patterns in these paintings. Another objective of this study is to verify the potential of 3D modelling as an analytical tool for the architectural spatiality of Caspar David Friedrich’s paintings. An analysis of the spatiality of the church designed by Frederich has been carried out through the reconstruction of the central nave of the religious space, as an example of the compositional patterns that will eventually be detected in his representation of Eldena Abbey. In this research, 3D modelling is a fundamental analytical tool used for reconstructing the spatiality of the church as represented by Friedrich in three artworks that have Eldena as their main reference for the architectural motif. This research uses the projection of the apparent contour to reconstruct the position and size of the depicted architectural elements within different reconstruction scenarios. The possibility of using a compositional benchmark as the ratio between the width of the column and the following intercolumnar distance allows using the identification of compositional patterns within the analysed artworks in order to understand how Friedrich conceived architectural space within them.